The Effect of the February 6 Earthquakes on Technopark Entrepreneurs: The Example of Malatya Technopark - Öztürk, Özge (Fırat University, 2025)
The earthquakes centered in Kahramanmaraş on February 6, 2023 negatively affected 11 provinces. More than 50 thousand people lost their lives after the disaster. Approximately 11 million people living in the region are trying to adapt to life after the earthquake. After the February 6 earthquakes, which were the most devastating earthquakes in the history of the Republic, there was a slowdown in economic activities in the region, and most businesses experienced problems such as working remotely, reducing production or service volume, having problems in their relations with suppliers or customers, qualified personnel leaving their jobs, and not being able to meet the need for qualified personnel, etc. In order to alleviate these problems, support packages were developed by the state and company officials who met the conditions benefited from these supports. Within the scope of this study, it is aimed to determine the situation of technopark companies that took innovative initiatives and had to survive by conducting R&D studies after the February 6 earthquakes. For this purpose, our study was conducted on companies operating within the Malatya Technopark. A 33-question survey was created to determine the changes that occurred in the companies after the earthquake. The online form of the developed survey was created, the contact information was shared with the company officials operating in Malatya Technopark and the data was collected. The collected data was analyzed with the help of SPSS (Statistical Package for the Social Sciences) program. In addition, data on the number of personnel, number of projects, etc. were obtained from Malatya Technopark Management. The findings based on all available data were interpreted and presented.

6 Şubat 2023 tarihinde meydana gelen Kahramanmaraş merkezli depremler 11 ili olumsuz etkilemiştir. Afet sonrası 50 bini aşkın kişi hayatını kaybetmiştir. Bölgede yaşayan yaklaşık 11 milyon kişi deprem sonrası hayata uyum sağlamaya çalışmaktadır. Cumhuriyet tarihinin en yıkıcı depremleri olan 6 Şubat depremleri sonrasında bölgede ekonomik faaliyetlerde de bir yavaşlama olmuş, çoğu işletme uzaktan çalışma, üretim veya hizmet hacmini küçültme, tedarikçileri veya müşterileri ile ilişkilerinde sıkıntı yaşama, nitelikli personelin işten ayrılması ve nitelikli personel ihtiyacını giderememe vb. sorunlar yaşamıştır. Bu sıkıntıları hafifletmek amacıyla devlet tarafından destek paketleri geliştirilmiş ve şartları sağlayan firma yetkilileri bu desteklerden faydalanmıştır. Bu çalışma kapsamında 6 Şubat depremleri sonrasında yenilikçi girişimde bulunan ve Ar-Ge çalışmalarını yürüterek ayakta kalmak zorunda olan teknokent firmalarının durumunun belirlenmesi amaçlanmaktadır. Bu amaç doğrultusunda çalışmamız Malatya Teknokent bünyesinde faaliyet gösteren firmalar üzerinde gerçekleştirilmiştir. Deprem sonrasında firmalarda meydana gelen değişiklikleri belirlemek üzere 33 soruluk bir anket oluşturulmuştur. Geliştirilen anketin çevrim içi formu oluşturularak, bağlantı bilgileri Malatya Teknokent’te faaliyet gösteren firma yetkilileri ile paylaşılmış ve veriler toplanmıştır. Toplanan veriler SPSS (Statistical Package for the Social Sciences) programı yardımıyla analiz edilmiştir. Ayrıca Malatya Teknokent Yön. A. Ş.’den personel sayısı, proje sayısı vs. veriler alınmıştır. Eldeki tüm verilere dayanarak ortaya çıkan bulgular yorumlanarak sunulmuştur.
6 Şubat Depremlerinin Teknokent Girişimcileri Üzerindeki Etkisi: Malatya Teknokent Örneği
Keywords: Disaster Economy; Afet Ekonomisi